Human milk microbial species are associated with infant head-circumference during early and late lactation in Guatemalan mother-infant dyads - Ajeeb, Tamara T.; Gonzalez, Emmanuel; Solomons, Noel W.; Koski, Kristine G. (Frontiers in Microbiology, 2022)
Human milk contains abundant commensal bacteria that colonize and establish the infant's gut but the association between the milk microbiome and head circumference during infancy has not been explored. For this cross-sectional study, head-circumference-for-age-z-scores (HCAZ) of vaginally delivered breastfed infants were collected from 65 unrelated Mam-Mayan mothers living in eight remote rural communities in the Western Highlands of Guatemala during two stages of lactation, "early" (6–46 days postpartum, n = 29) or "late" (109–184 days postpartum, n = 35). At each stage of lactation, infants were divided into HCAZ>=-1SD (early: n = 18; late: n = l1) and HCAZ<-1SD (early: n = 14; late: n = l9). Milk microbiome communities were assessed using 16S ribosomal RNA gene sequencing and DESeq2 was used to compare the differential abundance (DA) of human milk microbiota with infant HCAZ subgroups at both stages of lactations. A total of 503 ESVs annotated 256 putative species across the 64 human milk samples. Alpha-diversity using Chao index uncovered a difference in microbial community richness between HCAZ>=-1SD and HCAZ<-1SD groups at late lactation (p= 0.045) but not at early lactation. In contrast, Canonical Analysis of Principal Coordinates identified significant differences between HCAZ>=-1SD and HCAZ<-1SD at both stages of lactation (p = 0.003); moreover, 26 milk microbial taxa differed in relative abundance (FDR<0.05) between HCAZ>=-1SD and HCAZ<-1SD, with 13 differentially abundant at each lactation stage. Most species in the HCAZ>=-1SD subgroup were Streptococcus species from the Firmicutes genus which are considered human colonizers associated with human milk whereas the HCAZ<-1SD subgroup at late lactation had more differentially abundant taxa associated with environmentally and ‘potentially opportunistic species belonging to the Actinobacteria genus. These findings suggest possible associations between brain growth of breastfed infants and milk microbiome during lactation. Importantly, these data provide the first evidence of cross talk between the human milk microbiome and the infant brain that requires further investigation.